2001
DOI: 10.1007/s004230100252
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin kinetics in the early postoperative period of medullary thyroid carcinoma

Abstract: Using a highly sensitive calcitonin assay, we demonstrated that normalisation of basal calcitonin levels may be delayed in patients suffering from medullary thyroid carcinoma. The lack of correlation of preoperative levels and the time to normalisation of the basal calcitonin levels, as well as the positive pentagastrin test in some of the patients, argues that this phenomenon is not simply due to prolonged biochemical calcitonin elimination. Nevertheless, a prognostic influence could not be shown in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…In order to use it, one should not delay the serial Ct and CEA measurements after surgery. According to Brauckhoff et al [7], reliable Ct assessments are obtained one month after thyroidectomy in almost every patient. Notably, in high-risk patients, with short DT, we can obtain reliable DT estimation much more earlier - after one or two DTs, so when the post-surgery Ct or CEA concentration is elevated, subsequent measurements should be taken in relatively short intervals, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In order to use it, one should not delay the serial Ct and CEA measurements after surgery. According to Brauckhoff et al [7], reliable Ct assessments are obtained one month after thyroidectomy in almost every patient. Notably, in high-risk patients, with short DT, we can obtain reliable DT estimation much more earlier - after one or two DTs, so when the post-surgery Ct or CEA concentration is elevated, subsequent measurements should be taken in relatively short intervals, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, cases of detectable and even elevated postoperative CT levels after total tumor excision without apparent recurrence or metastases are documented abundantly (van Heerden et al 1990). Brauckhoff et al (2001) studied a 14-patient group and found pathological basal CT levels in only one of them 12 months later (Brauckhoff). They supposed that the delayed postoperative CT normalization and possibly CT stimulation, observed in some patients, could be an indicator for pre-or perioperative dissemination of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“… Lifelong follow‐up is recommended (4, D) . Key recommendation Postoperatively, calcitonin should be measured no earlier than 15 days after thyroidectomy and may take more than 2 months to fall to the lowest level . Response to primary surgery can be assessed clinically and by the measurement of serum calcitonin and carcinembryonic antigen (CEA) usually 6 months after surgery (4, D).…”
Section: Chapter 17mentioning
confidence: 99%